Mechanical and Physical Properties of Short Carbon Fiber and Nanofiller-Reinforced Polypropylene Hybrid Nanocomposites - Junaedi, Harri (Polymers (Basel), 2020)
The effect of various combinations of filler materials on the performance of polypropylene (PP)-based composites was investigated. PP in particulate form was used as the matrix. Milled short carbon fiber (SCF) micro-size, graphite nano-platelet (GNP), and titanium dioxide nanoparticles (nTiO(2)) were used as fillers. These fillers were incorporated in the polymer matrix to produce mono-filler (PP/SCF and PP/nanofiller) and hybrid composites. Hybrid composites consist of PP/10SCF/GNP, PP/10SCF/nTiO(2), and PP/10SCF/GNP/nTiO(2). The effect of the addition of SCF, GNP, and nTiO(2) on PP-based composites was investigated by analyzing their morphological, mechanical, and physical properties. The addition of mono-filler to the PP matrix improved the mechanical properties of the composites when compared to the neat PP. The ultimate tensile strength (UTS), flexural modulus, flexural strength, and impact toughness of the hybrid composites with 15 wt % total loading of fillers, were higher than that of mono-filler composites with 15 wt % SCF (PP/15SCF). A maximum increase of 20% in the flexural modulus was observed in the hybrid composite with 10 wt % of SCF with the additional of 2.5 wt % GNP and 2.5 wt % nTiO(2) when compared to PP/15SCF composite. The addition of 2.5 wt % nTiO(2) to the 10 wt % SCF reinforced PP, resulted in increasing the strain at break by 15% when compared to the PP/10SCF composite. A scanning electron microscope image of the PP/10SCF composite with the addition of GNP improved the interfacial bonding between PP and SCF compared with PP/SCF alone. A decrease in the melt flow index (MFI) was observed for all compositions. However, hybrid composites showed a higher decrease in MFI.